Lark & Kasim start a revolution - Callender, Kacen (Amulet Books, 2022)
Seventeen-year-old nurodivergent and nonbinary Lark pretends that they are the creator of a viral thread that their ex-best friend, Kasim, accidentally posted onto their Twitter account, declaring his unrequited love, but living a lie takes its toll on Lark, forcing them to deal with their own messy emotions.